Exotic massive 3D gravity - Ozkan, Mehmet; Pang, Yi; Townsend, Paul K. (Springer Science and Business Media LLC, 2018)
Abstract The linearized equations of “New Massive Gravity” propagate a parity doublet of massive spin-2 modes in 3D Minkowski spacetime, but a different non-linear extension is made possible by “third-way” consistency. There is a “Chern-Simons-like” action, as for other 3D massive gravity models, but the new theory is “exotic”: its action is parity odd. This “Exotic Massive Gravity” is the next-to-simplest case in an infinite sequence of third-way consistent 3D gravity theories, the simplest being the “Minimal Massive Gravity” alternative to “Topologically Massive Gravity”.
Keywords: Analogues of general relativity in lower dimensions; High Energy Physics - Theory; Eta-invariants, Chern-Simons invariants; Mathematical Physics; Chern-Simons Theories; Field Theories in Lower Dimensions; FOS: Physical sciences; QC770-798; General Relativity and Quantum Cosmology (gr-qc); Relativistic gravitational theories other than Einstein's, including asymmetric field theories; classical theories of gravity; General Relativity and Quantum Cosmology; High Energy Physics - Theory (hep-th); Nuclear and particle physics. Atomic energy. Radioactivity; Mathematical Sciences; Chern-Simons theories; field theories in lower dimensions; Classical Theories of Gravity; Physical Sciences; Particle and High Energy Physics